2020
DOI: 10.1016/j.jcot.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of extended length of stay after unicompartmental knee arthroplasty

Abstract: To identify factors that independently predict extended length of stay after unicompartmental knee arthroplasty (UKA) surgery (defined as length of stay longer than 3 days), and to identify factors predicting early post-operative complications. Methods: A retrospective analysis of all patients undergoing UKA from January 2016eJanuary 2019 at our institution was performed. Clinical notes were reviewed to determine the following information: Patient age (years), gender, American Society of Anesthesiologists (ASA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
2
16
1
Order By: Relevance
“…Preoperative patient characteristics such as old age, high ASA class, high body mass index, and female sex have repeatedly been shown to predict less likelihood of discharge on DOS after JRS, including PKR [ 33 36 ]. Recent studies have highlighted old age [ 4 , 36 , 37 ] and cardiovascular disease [ 4 , 37 ] as predictors of undesirable outcomes such as extended LOS, complication, and readmission. The same associating factors (age, ASA class, gender, and cardiovascular disease in particular) were repeated in this study of those not being discharged on DOS.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative patient characteristics such as old age, high ASA class, high body mass index, and female sex have repeatedly been shown to predict less likelihood of discharge on DOS after JRS, including PKR [ 33 36 ]. Recent studies have highlighted old age [ 4 , 36 , 37 ] and cardiovascular disease [ 4 , 37 ] as predictors of undesirable outcomes such as extended LOS, complication, and readmission. The same associating factors (age, ASA class, gender, and cardiovascular disease in particular) were repeated in this study of those not being discharged on DOS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other patient characteristics and preoperative comorbidity beyond high BMI and age might influence the risk of prolonged admission. In contrast, other studies have A study from the American College of Surgeons National Quality Improvement Program (ACS-NSQIP) reported that most UKA patients were obese and 9.2% were morbidly reported higher BMI to be associated with prolonged admission (Haughom et al 2015, Sephton et al 2020. Differences in variables included in the adjusted analyses as well as the adherence to fast-track principles could potentially contribute to the above-mentioned discrepancies.…”
Section: Readmission Within 90 Days Of Surgerymentioning
confidence: 93%
“…The few studies investigating the effect of BMI and age on LOS and readmission after UKA have varying conclusions. Some studies have associated higher BMI with increased risk of prolonged admission as well as short-term complications, while others find no such association (Otero et al 2016, Plate et al 2017, Sephton et al 2020. Likewise, day of surgery (DOS) discharge is reported to be less likely in older patients while some do not find this association (Haughom et al 2015, Matsumoto et al 2020.…”
mentioning
confidence: 99%
“…41 Recently, Sephton et al retrospectively evaluated prolonged LOS following UKA at their institution. 46 While significantly fewer patients ! 75 years of age were seen in the "fast track" group (LOS 3 days) compared with the "long stayers" group (LOS > 3 days), 14 and 30%, respectively, only ASA classes 3 to 4 and history of cardiovascular disease were found to be independent predictors of extended LOS following UKA in multivariable regression analysis.…”
Section: Hospital Length Of Staymentioning
confidence: 99%
“…75 years of age were seen in the "fast track" group (LOS 3 days) compared with the "long stayers" group (LOS > 3 days), 14 and 30%, respectively, only ASA classes 3 to 4 and history of cardiovascular disease were found to be independent predictors of extended LOS following UKA in multivariable regression analysis. 46 Finally, Jensen et al prospectively evaluated factors associated with continued postoperative hospitalization following "fast-tracked" UKA in 100 consecutive patients. 47 Pain and lack of mobilization were found to be the primary reasons recorded for not fulfilling discharge criteria.…”
Section: Hospital Length Of Staymentioning
confidence: 99%